Infection and Colorectal Neoplasm - Gontar Alamsyah Siregar; Sahat Halim; Ricky Rivalino Sitepu (The Indonesian Society for Digestive Endoscopy, 2015)
Colorectal cancer is a major cause of cancer-related morbidity and mortality. Colorectal cancer is the third most common malignancy and the 4th most common cause of cancer mortality worldwide. A number of infectious agents are considered to be cancer risk factors due to the hypothesis-generating and supportive evidence accumulated to date. It has been estimated that one fifth of all cancer is caused by some infectious agent(s). Infections from certain bacteria, such as Helicobacter pylori (H. pylori), Streptococcus bovis (S. Bovis), viruses, such as human papillomavirus (HPV), human cytomegalovirus (HCMV), and parasites may increase the risk of colorectal cancer. More studies are needed to learn the association of infectious agents with the incidence of colorectal cancer.Keywords: colorectal cancer, infectious agents, malignancy, neoplasms